Determination of the true water content, the nature of the impurities and their concentration in transformer oil - Gizzatova I.D.; Kozlov V.K.; Valiullina D.M. (E3S Web of Conferences, 2019)
During the operation of transformers, the insulating oil is aging, therefore, there is the deterioration of its insulating properties, which is determined by multiple physico-chemical processes. The most dangerous factor, from the point of view of preserving the operational reliability and resource of a power transformer, is the moisture content of the insulation. Most methods for determining moisture content have measurement errors. These errors are largely dependent on impurities that are contained in the oil. The modified Fisher method proposed in the article allows determining the amount of impurities in the oil and the absolute moisture content. Conducted research allows also to determine the composition of impurities, to reveal the relationship between impurities and some parameters of transformer oil.